Multi-objective optimal control: an overview - Gambier, Adrián; Badreddin, Essameddin (IEEE International Conference on Control Applications, 2007, 2007)
Optimization techniques have been a crucial tool for designing control systems and for tuning controllers. The always increasing quality requirements for new products and consequently the natural advance in control system design have lead to the introduction of more than one design criterion, which will require in turn more sophisticated techniques to solve such Multi-Objective Optimization (MOO) problems. Thus, many examples of using MOO techniques in control have appeared in the literature. In this paper, several optimal control design problems are analyzed from the MOO point of view. Moreover, some suggestions about how standard control design techniques can be extended to introduce multi-objective optimization are given.